2021
DOI: 10.3390/medicina57111139
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Atrial Fibrillation Recurrences after a First Radiofrequency Catheter Ablation Intervention for Paroxysmal Atrial Fibrillation—Experience of a Low Volume Ablation Centre

Abstract: Background and Objectives: Atrial fibrillation recurrences (AFR) after radiofrequency catheter ablation (RFCA) are not uncommon, up to 65% of patients having relapses in the first year. However, current data are based mainly on studies from centres with a large volume of ablations, as they include technically inhomogeneous interventions, and populations with different types of AF. The aim of our study was to assess and stratify the risk at 6 and 12 months for AFR after a single RFCA, in patients with paroxysma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A number of studies have identified some predictors of AF recurrence after catheter ablation methods, but their predictive level is insufficient. In this regard, this issue remains relevant and needs further research [19], [20], [21], [22], [23], [24], [25], [26].…”
Section: Rf and Cryoballoon Ablationmentioning
confidence: 99%
“…A number of studies have identified some predictors of AF recurrence after catheter ablation methods, but their predictive level is insufficient. In this regard, this issue remains relevant and needs further research [19], [20], [21], [22], [23], [24], [25], [26].…”
Section: Rf and Cryoballoon Ablationmentioning
confidence: 99%
“…This apnea-hypopnea index (i.e., OSA severity) independently predicts the risk of incident and recurrent AF (Zhao et al, 2018). Positive airway pressure (PAP) is the gold standard and the most recommended treatment for OSA, may reverse or mitigate atrial dysfunction, and is associated with a 42% relative risk reduction of recurrent AF (Matei et al, 2021). Further, recent observational evidence suggests that PAP may improve the efficacy of ablative and cardioversion therapies, decrease the cumulative burden of AF, and modify cardiovascular risk (Virani et al, 2021).…”
Section: Available Knowledgementioning
confidence: 99%